ENDORSER DAN BRAND AWARENESS DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN KOSMETIK PURBASARI (Studi Pada Mahasiswa Universitas Samawa Sumbawa Besar) - Sucihati, Roos Nana; Syauqi , M. Naufal Thoriq; Melyana, M (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to know the relationship between endorsers and brand awareness with the purchasing decision of Purbasari cosmetics among students of Samawa University, Sumbawa Besar. The type of this study was causal associative study which aims to examine the effect of endorsers (X1) and brand awareness (X2) on purchasing decisions of Purbasari cosmetics on students of Samawa University, Sumbawa Besar (Y). The type of data used in this study was quantitative data obtained directly from respondents using a questionnaire. Respondents in this study were students of Samawa University, Sumbawa Besar who had purchased Purbasari cosmetics, totaling 85 people who were selected using non-probability sampling techniques with the accidental sampling method (convenience sampling). The data analysis techniques used in this study include multiple linear regression analysis, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination testing (R2). The results of this study showed that endorsers and brand awareness had a positive and significant effect on the purchasing decision of Purbasari cosmetics among students of Samawa University, Sumbawa Besar, both partially and simultaneously. The ability of endorsers and brand awareness to explain the variation in changes in purchasing decisions of Purbasari cosmetics among students of Samawa University, Sumbawa Besar was 41.6%, while the remaining of 58.4% was effected by other factors outside this research model, such as personal factors, social class factors, and reference group factors.